The Influence of Lifestyle in Coastal Communities on the Incidence of Hypertension in Southeast Sulawesi: A Review - Febriana Muchtar; Thiufatin Terezky Brilyanti; Orin Widiarti (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: According to the World Health Organization, lifestyle refers to a way of living that is shaped by identifiable behavioral patterns. It is influenced by a combination of social factors, individual characteristics, living environments, and socio-economic conditions. WHO has also identified a sedentary lifestyle as one of the leading risk factors for mortality worldwide, with hypertension being one of the most common health conditions associated with physical inactivity. Objective: This study aims to identify lifestyle factors that contribute to the incidence of hypertension in coastal communities of Central Sulawesi, Indonesia. Methods: This research employed a literature review approach, analyzing both Indonesian and international peer-reviewed journal articles. The selection focused on studies that explored the relationship between lifestyle and hypertension, particularly in coastal regions. Results: The analysis of the reviewed literature consistently demonstrates that lifestyle factors play a significant role in the development of hypertension. Across the selected studies, key risk factors identified include lack of physical activity, unhealthy dietary habits, alcohol consumption, and low levels of education. Conclusion: Based on the review of 21 relevant research articles, lifestyle emerges as a major determinant in the incidence of hypertension. Contributing factors include physical inactivity, poor nutrition, alcohol use, and educational level. In addition, age and family history are also influential in increasing hypertension risk. Importantly, the findings highlight that improved knowledge and better access to healthcare services can enhance efforts toward hypertension prevention, particularly in underserved coastal communities. Keywords: Sedentary Behavior, Lifestyle, Hypertension, Healthcare Access, Indonesia